Community‑based ART distribution system can effectively facilitate long‑term program retention and low‑rates of death and virologic failure in rural Uganda - Okoboi, Stephen; Ding, Erin; Persuad, Steven; Wangisi, Jonathan; Birungi, Josephine; Shurgold, Susan; Kato, Darius; Nyonyintono, Maureen; Egessa, Aggrey; Bakanda, Celestin; Munderi, Paula; Kaleebu, Pontiano; et al. (AIDS research and therapy, 2015)
Community-drug distribution point is a care model for stable patients in the community designed to make ART delivery more efficient for the health system and provide appropriate support to encourage long-term retention of patients. We examined program retention among ART program participants in rural Uganda, which has used a community-based distribution model of ART delivery since 2004. Methods: We analyzed data of all patients >18 years who initiated ART in Jinja, Ugandan site of The AIDS Support Organization between January 1, 2004 and July 31, 2009. Participants attended clinic or outreach visits every 2–3 months and had CD4 cell counts measured every 6 months. Retention to care was defined as any patient with at least one visit in the 6 months before June 1, 2013. We then identified participants with at least one visit in the 6 months before June 1, 2013 and examined associations with mortality and lost-to-follow-up (LTFU). Participants with >4 years of follow up during August, 2012 to May, 2013 had viral load conducted, since no routine viral load testing was available. Results: A total of 3345 participants began ART during 2004–2009. The median time on ART in June 2013 was 5.69 years. A total of 1335 (40 %) were residents of Jinja district and 2005 (60 %) resided in outlying districts. Of these, 2322 (69 %) were retained in care, 577 (17 %) died, 161 (5 %) transferred out and 285 (9 %) were LTFU. Factors associated with mortality or LTFU included male gender, [Adjusted Hazard Ratio (AHR) = 1.56; 95 % CI 1.28–1.9], CD4 cell count <50 cells/μL (AHR = 4.09; 95 % CI 3.13–5.36) or 50–199 cells/μL (AHR = 1.86; 95 % CI 1.46–2.37); ART initiation and WHO stages 3 (AHR = 1.35; 95 % CI 1.1–1.66) or 4 (AHR = 1.74; 95 % CI 1.23–2.45). Residence outside of Jinja district was not associated with mortality/LTFU (p value = 0.562). Of 870 participants who had VL tests, 756 (87 %) had VLs <50 copies/mL. Conclusion: Community-based ART distribution systems can effectively mitigate the barriers to program retention and result in good rates of virologic suppression.
Keywords: Antiretroviral therapy; Virologic failure; Lost-to-follow-up; mortality; Retention; Sub-Saharan Africa; Uganda